A comparative review: Physicochemical properties and antioxidant activities of stingless bees (Heterotrigona itama & Geniotrigona thoracica) and honey bee (Apis mellifera) honey / Nur Nael ‘Awateef Harun and Mohd Hilmi Hassan - Harun, Nur Nael ‘Awateef; Hassan, Mohd Hilmi (2021)
Numerous studies regarding the physicochemical and antioxidant properties of stingless bee honey have been carried out and commonly compared with the honey bee, Apis mellifera honey. The various compositions in each species may affect the purity and originality of the honey thus comparing the honey properties are essential. The properties are capable of determining the quality of honey. This review evaluates and compares the physicochemical and antioxidant properties of honey samples produced by three different bee species namely Heterotrigona itama, Geniotrigona thoracica and Apis mellifera. The bee species were classified into two major groups, stingless bee, H. itama and G. thoracica and honey bee, A. mellifera. Both physicochemical and antioxidant properties of honey were different according to their bee species. The physicochemical analysis includes moisture content, ash content, colour characteristic, pH, free acidity, total soluble solids (TSS), and several antioxidant analysis including total phenolic content (TPC), total flavonoid content (TFC), free radical scavenging activity (DPPH) and ferric reducing antioxidant power (FRAP). The results from the different authors showed that stingless bee honey possessed significantly higher moisture content, ash content, colour characteristic, free acidity, TPC, TFC, DPPH and FRAP compared to the honey bee, A. mellifera honey which exhibited higher pH and total soluble solids (TSS). Among the stingless bee honey samples, H. itama honey exhibited higher ash content, colour characteristic, free acidity, TPC and FRAP while G. thoracica honey possessed higher moisture content, pH, total soluble solids (TSS), TFC and DPPH. Bee species fundamentally affect the physicochemical properties and antioxidant activities of honey samples.